2016
DOI: 10.1515/aiht-2016-67-2774
|View full text |Cite
|
Sign up to set email alerts
|

Workplace noise exposure and serum testosterone in men enrolled in the 1999-2004 National Health and Nutrition Examination Survey

Abstract: There is compelling evidence from animal experiments that noise exposure suppresses testosterone in males by affecting the hypothalamic-pituitary-testicular axis. Virtually nothing is known about its effect in humans. Therefore, the aim of this study was to explore the association between occupational noise exposure and serum testosterone in a representative sample of the general population. The sample has been taken from the National Health and Nutrition Examination Survey (NHANES) data for the period between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…In the current study the total and free testosterone levels were significantly lower among workers exposed to noise level above 85dB.The levels of serum total and free testosterone levels were lower in 15 workers (28.8%) of group A for both parameters compared to group B who were completely normal and the differences were statistically significant (p< 0.05) as shown in (Table 3). Dzhambov (2016) reported in his study on chronic noise exposure and testosterone deficiency that exposure to loud noise was associated with lower TT, but the effect was statistically significant only among those aged ≥37 years. Also, study done by Chamkoori et al (2015) on the effect of noise stress on the hormonal and semen analysis parameters in industrial workers of Bushehr, Iran showed a significant decrease in concentration of testosterone, LH and FSH and major changes in sperm parameters among workers exposed to noise from 85dBA to 119 dBA.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the current study the total and free testosterone levels were significantly lower among workers exposed to noise level above 85dB.The levels of serum total and free testosterone levels were lower in 15 workers (28.8%) of group A for both parameters compared to group B who were completely normal and the differences were statistically significant (p< 0.05) as shown in (Table 3). Dzhambov (2016) reported in his study on chronic noise exposure and testosterone deficiency that exposure to loud noise was associated with lower TT, but the effect was statistically significant only among those aged ≥37 years. Also, study done by Chamkoori et al (2015) on the effect of noise stress on the hormonal and semen analysis parameters in industrial workers of Bushehr, Iran showed a significant decrease in concentration of testosterone, LH and FSH and major changes in sperm parameters among workers exposed to noise from 85dBA to 119 dBA.…”
Section: Discussionmentioning
confidence: 95%
“…The hypothalamic-pituitary-testicular (HPT) axis is sensitive to gonadotropic hypogonadism. Occupational and environmental noise act as stressors and stimulate the HPA (Hypothalamicpitutary-axis), and have been implicated as a risk factor for testosterone deficiency (Dzhambov et al, 2015) Occupational noise exposure was associated with significantly lower total and free testosterone in active male workers aged 16-85+ years in the US general population (Dzhambov, 2016). Low testosterone is a risk factor for cardiovascular disease, obesity, diabetes, bone mineral density loss, depression, impaired cognitive and social functioning, and overall mortality (Zarotsky et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Min and Min in 2017 found that after controlling for age, residential area, and other lifestyle factors, while small 1 decibel increases in daytime or nighttime noise was not associated with increased risk of infertility, men exposed to increased noise levels at the second to fourth quartile had significantly increased odds of infertility (P<0.05) (87). It was hypothesized that increased risk for infertility in men exposed to high levels of noise pollution may be due to activation of stress responses and alterations in the hypothalamic-pituitary-gonadal (HPG) axis with ultimate suppression of testosterone (87,88).…”
Section: Noise Pollutionmentioning
confidence: 99%